Use of surgical grafting as a part of multidisciplinary treatment for a patient treated with fixed orthodontic therapy to improve treatment outcomes - Hoang Viet; Tran Hong Phuoc; Hoang Ming Tuyen; Anand Marya (Clinical Case Reports, 2024)
Key Clinical Abstract Multidisciplinary treatment options can help provide good clinical outcomes if these are appropriately sequenced and carried out correctly. This case exemplifies interdisciplinary involvement to ensure the patient received an improved esthetic outcome. Abstract The presence of anterior diastemas may compromise the esthetics of a patient's smile, causing mental, and social trauma in many patients. After careful evaluation Periodontal, surgical, and prosthodontic treatments are sometimes required to ensure successful treatment outcomes using a multidisciplinary staged treatment approach. These approaches must be carefully planned to ensure timely treatment progress. Surgical intervention must be planned at the right point in treatment to ensure adequate healing before placement of esthetic restorations.